The Five Main Values of Strengthening Character Education (PPK) in Umar bin Khattab - Yoga Anjas Pratama (Journal of Contemporary Islamic Education, 2022)
The value of character education is standards of human behavior in the life of society and the state. Ministry of Education and Culture of the Republic of Indonesia has declared five main values of strengthening character education (PPK) as the axis of education, namely: religious, nationalist, independent, mutual cooperation and integrity. These five values basically exist in Umar bin Khattab. For that in this research will be studied in more depth related the five main values of character education in Umar bin Khattab. This research is a library research conducted by means of descriptive analysis to data sources, in the form of: articles, books and related documents. The result of this research is that there are five values of character education in Umar bin Khattab, consist of: (1) Religious: attitude of fear and obedience to Allah's commands, love of nature and tolerance (2) Nationalist: excellent and achievers, appreciate achievements, obey the law and care about social (3) Independent: disciplined, hardworking and brave (4) Mutual cooperation: cooperation, helping each other and likes to consult (5) Integrity: love of truth, love of peace, fair, honest, responsible, gentle and generous.